Photometric Segmentation: Simultaneous Photometric Stereo and Masking - Haefner, Bjoern; Queau, Yvain; Cremers, Daniel (Proceedings - 2019 International Conference on 3D Vision, 3DV 2019, 2019)
This work is concerned with both the 3D-reconstruction of an object using photometric stereo, and its 2D-segmentation from the background. In contrast with previous works on photometric stereo which assume that a mask of the area of interest has been computed beforehand, we formulate 3D-reconstruction and 2D-segmentation as a joint problem. The proposed variational solution combines a differential formulation of photometric stereo with the classic Chan-Vese model for active contours. Given a set of photometric stereo images, this solution simultaneously infers a binary mask of the object of interest and a depth map representing its 3D-shape. Experiments on real-world datasets confirm the soundness of simultaneously solving both these classic computer vision problems, as the joint approach considerably simplifies the overall 3D-scanning process for the end-user.
CRIS-Team Scopus Importer:2023-03-08
Keywords: 3D Reconstruction; Photometric Stereo; Segmentation; Variational Methods